DC SQUID series array amplifiers with 120 MHz bandwidth (corrected). - Huber, M.E (IEEE Transactions on applied superconductivity)
We report on the performance of dc SQUID (Superconducting Quantum Interference Device) series array amplifiers from dc to 500 MHz. The arrays consist of up to 100 dc SQUIDs, with varying degrees of intracoil damping; the flux focusing washer of each SQUID is electrically isolated from the SQUID loop (Lsq=18 pH). Using an rf network analyzer, we have observed high-frequency resonances in the response at bias points corresponding to distortions in the dc transfer functions. Increasing distance between SQUIDs in the array reduces the distortions. Distortions are also more pronounced, and bandwidth reduced, in devices incorporating the flux-focusing washer into the SQUID body. With intracoil damping of 0.25 Ω per turn on the input coil, the voltage-flux transfer characteristics of the isolated-washer design and 300 pm center-to-center SQUID spacing are free of significant distortions, and the bandwidth is not degraded compared to undamped devices. The 100-SQUID array has 150 nH input inductance, 500 V/A transimpedance, 2.5 pA/√Hz equivalent input current noise at 4 K, and 120 MHz bandwidth